Impact of COVID-19 on undergraduate business students: a longitudinal study on academic motivation, engagement and attachment to university. Issue 2 (18th December 2020) - Pasion, Rita; Dias-Oliveira, Eva; Camacho, Ana; Morais, Catarina; Campos Franco, Raquel
Abstract : Purpose: This study aims to explore whether the COVID-19-related circumstances hindered these academic-related variables. Design Methodology Approach: The authors surveyed two groups of undergraduate business students (42% male) who completed the questionnaires at the beginning and at the end of the semester. One group of students attended only face-to-face classes in the 2018/2019 academic year ( n = 126) and the other group transitioned to online classes because of the COVID-19 outbreak in the 2019/2020 academic year ( n = 99). Findings: The findings show no statistically significant group differences between the pre- and post-test in students' intrinsic and extrinsic motivation, feelings of attachment to the university and engagement dimensions of absorption and vigour. Nevertheless, a moderate negative effect was found in the dedication engagement dimension. Practical Implications: The authors discuss the main results in terms of some practices that may contribute towards attenuating the effects of future emerging pandemics in the higher education setting. Originality Value: The COVID-19 pandemic imposed a rapid transition to online instruction in education institutions worldwide. However, it remains unclear to date how students' engagement, motivation and attachment to the university were negatively affected by the first COVID-19 outbreak.